2014
DOI: 10.1155/2014/254612
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Colorectal Resection in Kidney Transplant Recipients: Technical Tips, Short- and Long-Term Outcomes

Abstract: Aim. To prove the safety and feasibility of minimally invasive (laparoscopic and robotic) colorectal resection in kidney recipients by evaluating the technical protocol and reviewing short- and long-term outcomes. Methods. Between May 2007 and August 2012, a retrospective review of ten kidney transplant patients diagnosed with colorectal cancer was evaluated for technical tips, short- and long-term outcomes. Results. The mean patients' age was 56.8 ± 9.91 years and 50% of them were male. Anterior and low anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Four cases involving laparoscopic surgery for colorectal cancer after kidney transplantation have been reported [7][8][9][10] by a case series comprising 19 patients with colorectal cancer after kidney transplantation who underwent laparoscopic or robotic surgery (Table 1). One kidney transplantation was performed for each of these four cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cases involving laparoscopic surgery for colorectal cancer after kidney transplantation have been reported [7][8][9][10] by a case series comprising 19 patients with colorectal cancer after kidney transplantation who underwent laparoscopic or robotic surgery (Table 1). One kidney transplantation was performed for each of these four cases.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term prognosis was also favorable. Alasari et al [7] reported that among the 10 patients who underwent laparoscopic or robotic surgery for colorectal cancer after kidney transplantation, the three-year disease-free rate was 83.3%, and the three-year overall survival rate was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, transplant recipients seem to benefit more from the minimal access approach. Alasari [ 26 ] evaluated short- and long-term outcomes of minimally invasive (laparoscopic and robotic) colorectal resection in 10 kidney transplant recipients with CRC between May 2007 and August 2012. Having observed a favorable result in operative time (192.5 ± 15 min), blood loss (30 ± 50 mL), and postoperative complication (2/10 minor complications), they proposed minimally invasive colorectal procedures could be considered as safe and feasible alternatives to open colorectal resection in kidney transplant patients.…”
Section: Discussionmentioning
confidence: 99%